Investigations of the Antimicrobial Effectiveness of Different Disinfection Protocols Against Endodontic Pathogens in Root Canal Systems - Hitesh Chohan; Sanjana Khullar; Ria H Patel; Jyotirmayee Rath; Sameera Mohammed; Savadamoorthi Kamatchi Subramani (Journal of Pharmacy and Bioallied Sciences)
Objective: To compare the antimicrobial effectiveness of erbium-doped yttrium-aluminum-garnet (Er: YAG) laser, ozone therapy, photodynamic therapy (PDT), and sodium hypochlorite against endodontic pathogens. Methods: Standardized root canal models inoculated with Enterococcus faecalis, Pseudomonas aeruginosa, and Candida albicans were treated with Er: YAG laser, 5.25% NaOCl, ozone, or PDT with methylene blue. Microbial loads, treatment time, and depth of penetration were assessed. Results: Er: YAG laser demonstrated the highest efficacy against Enterococcus faecalis and Pseudomonas aeruginosa, followed by PDT. Effects on Candida albicans were not statistically significant across treatments. Er: YAG achieved the greatest depth of penetration, while PDT required the longest application time. Conclusions: Laser and photodynamic therapies show promise as alternatives to traditional chemical disinfection in endodontics, potentially improving treatment outcomes. Further research is needed to optimize these protocols for clinical use.